PMO-153 Hepatitis A virus vaccination in persons with hepatitis C virus infection: consequences of implementation in low incidence areas. (28th May 2012) - Rowe, I A; Parker, R; Armstrong, M J; Houlihan, D D; Mutimer, D
Abstract : Introduction: Hepatitis A virus (HAV) superinfection in persons with hepatitis C virus (HCV) infection has been associated with a high mortality rate. Consequently HAV vaccination is recommended by many authorities for this patient group. The incidence of HAV is low and has been reducing in many areas, including Western Europe and the USA. The aim of this study was therefore to determine the cost and clinical consequences of routine vaccination in persons with HCV infection. Methods: To determine the mortality risk of HAV superinfection a meta-analysis including studies reporting mortality in HCV infected persons was done using RevMan 5.1 (Cochrane Collaboration). Data were extracted independently by two investigators and recorded on a standardised spreadsheet. The pooled mortality estimate was used to determine the number needed to vaccinate (NNV) to prevent mortality from HAV. The total vaccine cost was also calculated. Baseline mortality and cost data from the US were used as an example. Results: 239 studies were identified using a defined search strategy. From those, 11 appeared to be relevant to the study and of these 7 were suitable for inclusion in the meta-analysis. The pooled OR for mortality risk in HAV superinfection of HCV infected persons was 7.23 (95% CI 1.24 to 42.12) with significant heterogeneity ( I 2 =56%, p=0.03) between studies. Case-fatality rates are however low, and in the US at the last estimate (2007) the number of deaths from HAV in the general population was 34 per year (0.2/1 000 000 population). Using the pooled OR for mortality that translates to 1.4 deaths per 1 000 000 susceptible persons with HCV per year. The NNV to prevent 1 death per year is therefore 814 849 assuming 90% vaccine uptake and 94.3% vaccine efficiency. The vaccine cost for this totals $162 million, or $80.1 million per death prevented per year. Conclusion: These data challenge the utility of routine HAV vaccination in HCV infected persons and its incorporation into clinical practice guidelines. HAV vaccination of all HCV infected persons in low incidence areas is likely to expose many individuals to an intervention that is of no direct benefit. Competing interests: None declared.